Reingeniería en la distribución de planta para el aumento de productividad de la empresa “Agroindustrias Montenegro”. - Zuikan Alarcón, Katherine Alicia (2021)
This project presents a proposal for plant distribution reengineering in the production line of two-valve conveyor heads with pneumatic piston at the company “Agroindustrias Montenegro”, located in Santo Domingo de los Tsáchilas. Currently, it has distribution problems in the plant, so an internal analysis of the company was carried out using the matrix: Internal Capacity Profile (PCI), which is in charge of measuring the managerial, competitive, financial, technological and human talent capacity. Their weaknesses, opportunities, strengths and threats were also determined with a SWOT diagram. This research was carried out by applying the plant distribution methodology (Sistematyc Layout Planning). In order to carry it out, several stages must be fulfilled, we proceeded to give names to the workstations and locate them depending on their proximity value with the help of a work relationship diagram. The time study was carried out by timing and observing four conveyor heads on a time sheet, with which the normal time and standard time were obtained at each of the work stations to then make the total summation and thus obtain the typical time of the process, thus determining the bottlenecks and giving the pertinent improvements in each station. A simulation of the process was carried out in the FlexSim software which yielded data on the necessary times of the plant distribution and the optimization of each of the processes.